Determination of the critical hydrophile-lipophile balance of licuri oil from Syagrus coronata: application for topical emulsions and evaluation of its hydrating function - Leila Bastos Leal; Giovana Damasceno Sousa; Karoline Belém Seixas; Pedro Henrique Nogueira de Souza; Davi Pereira de Santana (Universidade de São Paulo, 2013)
The aims of this study were to determine the critical hydrophile-lipophile balance (HLB) of licuri oil, and to perform a clinical assay to evaluate its hydrating effects. For the determination of the HLB, serial emulsions were prepared with the oil. Regarding the clinical study, 13 human subjects were recruited to evaluate the hydrating power of the emulsified preparation containing licuri oil, and comparing it with the same preparation containing sweet almond oil (SAO). The critical HLB of licuri oil was represented by the zones within the concentrations of 10% for the oil and 15% for the pair of tensoactive agents, with a value of 11.8. Both preparations showed similar hydrating power. We propose that licuri oil can be considered a new lipophilic adjuvant with hydrating characteristics, which can be used in cosmetic preparations, replacing consecrated oils, such as SAO. O objetivo deste estudo foi determinar o EHL crítico do óleo licuri e realizar um ensaio clínico para avaliar os seus efeitos hidratantes. Para a determinação do EHL foram preparadas emulsões seriadas contendo esse óleo. Em relação ao estudo clínico, avaliamos o poder hidratante de preparação emulsionada com óleo de licuri, comparando-a com a mesma preparação contendo óleo de amêndoas doces (OAD), em 13 voluntários. O EHL crítico do óleo de licuri foi representado pelas zonas dentro das concentrações de 10% para o óleo e 15% para o par de tensoativos, com um valor de 11,8 e ambas as preparações mostraram poder hidratante similar. Desta forma, o óleo de licuri pode ser considerado um novo adjuvante lipofílico com função hidratante, o qual pode ser usado em preparações cosméticas, substituindo óleos de consagrado uso, tais como o OAD.